The Return of the Gods – Retrieving the Archetype Concept in Sociological Thinking - Secondulfo, Domenico (Italian Sociological Review, 2026)
This essay aims to investigate the various meanings of archetype and the criticisms of its use in scientific analysis, putting forward a proposal for its use in the socio-anthropological analysis of social culture.